Exploration of effects of galvanic vestibular stimulation on circadian rhythms and its associations with sleep and spatial memory in patients with breast cancer: The ICANSLEEP-2 protocol. - Melvin Galin; Laura de Girolamo; Bénédicte Clarisse; Carine Segura-Djezzar; Franka Glöckner; Clara Elia; Stéphane Réhel; Patrice Clochon; Franck Doidy; Julien Chavant; Olivier Etard; Fausto Viader; et al. (PLoS ONE)
Background Patients with breast cancer (BC) exhibit circadian rhythm disruptions, mainly of rest-activity rhythm (RAR), of which sleep is an essential component, and cortisol rhythm. Sleep complaints such as insomnia and cognitive impairments are prevalent in BC. In general population, sleep is known to contribute greatly to cognition. Thus, improving RAR (and particularly sleep) could help limiting cognitive impairments in BC patients. It has recently been suggested that, in addition to its essential role in spatial memory, the vestibular system contributes to RAR synchronization. Its stimulation could therefore limit both sleep disturbances and spatial memory deficits in BC. Objectives The main aim of the ICANSLEEP-2 study is to assess the effects of galvanic vestibular stimulation (GVS) on circadian rhythms. The secondary aim is to assess whether GVS improves sleep and spatial memory in BC patients. Methods Two groups with insomnia complaints (Insomnia Severity Index > 7) will be included: a patients' group with BC (n = 50) and a healthy control group without history of cancer (n = 25). There will be two assessment sessions, before and after 2 weeks of GVS. Patients will be randomly assigned to either a GVS group or a sham group (noneffective stimulation). Controls will receive GVS. GVS effects will be quantified and compared between groups. Assessments will include actigraphy, salivary cortisol, polysomnography, a cognitive test battery (including a computer-based task for spatial memory) and validated questionnaires (for psychological functioning and sleep complaints). Discussion Current methods for improving sleep in BC have had controversial outcomes regarding sleep structure. We expect GVS to offer a new mean of directly targeting RAR disruptions in BC patients, with beneficial effects on sleep structure. Given the crucial impact of sleep on cognitive functioning, notably spatial memory, improving sleep of BC patients should enhance their cognitive functioning. Ethics and dissemination This study received ethical approval from the Ile de France IV institutional review board on 19 April 2022 (no. ID-RCB: 2022-A00437-36). The findings yielded by this protocol will be presented at various conferences and in peer-reviewed journals. Clinicaltrials.gov registration number NCT05414357.